How to think about the clear-sky shortwave water vapor feedback - Florian E. Roemer; Stefan A. Buehler; Kaah P. Menang (npj Climate and Atmospheric Science)
Abstract Earth’s climate feedback quantifies the response of Earth’s energy budget to temperature changes and thus determines climate sensitivity. The climate feedback is largely controlled by water vapor which absorbs both longwave radiation emitted by Earth and shortwave radiation from the Sun. For the clear-sky shortwave water vapor feedback λ SW, a gap remains between process understanding and estimates from comprehensive climate models. Therefore, we present a hierarchy of simple models for λ SW. We show that λ SW is proportional to the change with temperature in the square of atmospheric transmissivity that depends on the atmospheric concentration of water vapor and its ability to absorb shortwave radiation. The global mean λ SW is well captured by a simple analytical model that approximates the strong spectral variations in water vapor absorption, whereas its temperature dependence results from spectral details in water vapor absorption. With this study, we expand the conceptual understanding of an important but understudied feedback component.